The Effect of Self-Regulated Learning on Student Academic Procrastination - Amelia Dwi Astuti (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
Background: This also happens to PGSD students. Based on observations, show that the majority of students have carried out academic procrastination such as delaying doing coursework, delaying studying when facing exams, and sometimes choosing to do things that are more fun and unrelated to academic assignments. The emergence of academic procrastination behavior is caused by several factors, including low intrinsic motivation, laziness in studying, lack of discipline in the way parents educate them, influence from friends in their environment, as well as a lack of self-regulated learning (SRL) in managing time for doing assignments with other things. Aim: This study aims to determine the effect of self-regulated learning on academic procrastination of Muhammadiyah University students of Palangkaraya. Method: This type of research is quasi-experimental research. The population of this study was 2714, while the sample was 349 students. Data were collected by using several instruments in the form of an academic procrastination scale and a self-regulated learning scale. Statistical testing using linear regression analysis. Results and Dıscussion: The results of the study indicated that the significance value is 0.025 <0.05. Conclusion: It can be concluded that there is a significant influence on the self-regulated learning on academic procrastination of Muhammadiyah University students of Palangkaraya.